Estado emocional del cuidador de una persona con discapacidad y su influencia en las relaciones interpersonales - Vargas Burgos, Jorge Dionicio (2020)
This case study aimed to determine the emotional state of the caregiver of a person with disabilities and their influence on interpersonal relationships. Taking into account these antecedents, the emotional and interpersonal relationships variables, he lets us notice a clear social isolation, in addition to the extreme care he has with his daughter, makes interpersonal relationships even more complicated, having as one of the main findings the anxious type adaptation disorder. The inerviews carried out with the mother and the social worker of (MIES) were very helpful, after the interviews the following tests were carried out: Hamilton anxiety inventory, Beck depression inventory, Inadaptation scale –EI-. Signs and symptoms manifested by the patient are importance of the psychodiagnostic process that helps determine all those repercussions in the emotional and social área of patient.